Diesel Hybrid Powertrain Concept Study for Long Truck Combinations - Umasankar, Ashwinkumar; Mehta, Devansh (My University, 2014)
The commercial vehicle industry faces strong challenges in the forthcoming years; such as reducing the dependency on fossil fuels, lowering energy consumption, fulfilling stricter legislation regarding emissions and also increased congestion on the roads. Thus, there is a high demand for more economically and environmentally viable transport solutions. Long haul applications are interesting for fuel consumption reduction studies, due to the fact that even 1-2% reduction in fuel consumption can result in significant savings, since the distances and the mileage in context are large. The current hybridization and downsizing of existing combustion engines for long-haul applications can lead to decreased fuel consumption, but not enough to motivate the higher cost of the hybrid powertrain. Also, it is not favoured by the market as it affects the vehicle’s longitudinal propulsion performance. Hence, longer vehicle combinations are being evaluated, as they lead to less energy consumption per unit of mass transported, because of increased cargo carrying capacity. The market will also have the advantage of saving in labor costs such as driver wages because fewer drivers are needed to transport the cargo capacity in question. The thesis aims to electrify an intermediate unit in a typical long combination, called a dolly, and simulate the resulting powertrain. Feasibility studies are conducted for packaging the resulting components from powertrain sizing. 5 different concepts are constructed for the Dolly powertrain from the selected components. Rule-based control strategies are formulated for the concepts, which have a layout comparable to that of a Parallel Hybrid. The powertrain models are combined with the vehicle dynamics model of the long combination to create a simulation platform, and typical vehicle maneuvers are studied. Results in terms of fuel consumption and performance related parameters are recorded and compared for the different concepts. Conclusions are derived from the results and the most interesting concepts for different parameters are evaluated and presented.
Keywords: Transport; Farkostteknik; Transport; Vehicle Engineering